Strategi Guru dalam Mengembangkan Kreativitas Seni Rupa Tiga Dimensi Siswa di Min Sibuhuan - Arfin Hasibuan; Ummi Salamah Nasution; Lina Mayasari Siregar (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to analyze the development of three-dimensional art creativity of fifth-grade students and describe teacher strategies in developing three-dimensional art creativity at MIN Sibuhuan. This study uses a qualitative descriptive method. Data were collected through observation, interviews, and documentation involving teachers and fifth-grade students of MIN Sibuhuan as informants. Data were analyzed qualitatively through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the three-dimensional art creativity of fifth-grade students of MIN Sibuhuan is in the good category. Students have demonstrated the ability to understand the basic concepts of three-dimensional art, have imagination in their work, and are able to utilize various materials to produce works. However, there are still obstacles such as limited learning media, lack of appreciation space, and low originality of some students. Teacher strategies in developing creativity are carried out through project-based learning, contextual approaches, utilization of natural and recycled materials, providing freedom of expression, mentoring as facilitators, and the application of holistic assessment. Although there are obstacles such as limited time, facilities, and student self-confidence, the strategies implemented are able to encourage students' creativity, independence, and courage in expressing themselves. In conclusion, participatory, contextual, and creative process-oriented learning strategies contribute positively to the development of students' three-dimensional fine arts creativity at MIN Sibuhuan.